P-23 Enhanced end-of-life care decision making (EELCD): An interventional study toward advance care planning and difficult discussions at two ontario hospital sites. (1st September 2015) - Kachuik, L; Welsh, C; Klinger, C; Foreman, T; Scott, J; Wheatley-Price, P; Wooller, K; Pereira, J
Abstract : Background: Coinciding with an ageing population and changing death trajectories, expectations toward health care systems to sustainably meet needs and demands are heightened. Advance care planning (ACP) and the early introduction of palliative care are viewed to enhance quality of life, to result in better end-of-life decision making and lower high intensity health care utilisation, especially at the hospital level. Aims: Determine the prevalence of ACP and its documentation [via chart review]; Elicit satisfaction with end-of-life communication and decision-making from the patients' and families' perspectives [via semi-structured questionnaire]; Identify barriers and facilitators to improving the quantity and quality of ACP [ibid]; and Investigate the implications of ACP on care outcomes and costs [via case report form]. Methods: Observational, cross-sectional, pre-post study at two hospital sites in the Province of Ontario (Canada) incorporating Knowledge-to-Action loops to enhance end-of-life care decision making by patients and their families, and communication flow from the health care provider side. A "Difficult Discussions" educational program was employed as an 'intervention'. Study Population: Consecutive patient-primary caregiver dyads in two cycles (2014 and 2015), and health care professionals at the two sites. Results: ACP and written documentation of treatment wishes levels were generally low (<40%) and concordance between patients' expressed preferences and documented goals of care was about 19%. Benchmarked site reports revealed further ACP information needs, also linked to information about prognosis. Scope of practice questions surfaced within the interdisciplinary teams. Discussion/conclusion: Further knowledge translation activities are needed also in connexion with National Advance Care Planning Day .